Swearword in Steinbeck’s Novel “Of Mice and Men” and Its Indonesian Translated Version Toer’s “Tikus dan Manusia” - Eka Jayanti Nurhasanah; Sape'i Sape'i; Deuis Sugaryamah (CALL, 2019)
Of Mice and Men is a novel written by John Steinbeck,  published in 1937. It tells about the story of George Milton and Lenny Small, two displaced migrant ranch workers, who move from place to lace in California in searching of a new job opportunities during the Great Depression in the United States. The novel is translated to Indonesian by Pramoedya Ananta Toer in “Tikus dan Manusia. So, it seems fun to analyse how the translator transfer meaning from source language to target language, especially in translating swearword which is found in the novel. The researcher used Hudges’s (1991) theory about swearword and Molina and Albir (2005), and Fawcet(1997) about translation techniques used by the translator. From the analysis, the researcher found 9 data of imbecile term for nuts, cuckoo, and ain’t bright, 23 data general terms for bastard and crazy, 39 data of death terms for the hell and goddamn, 6 data of mother in law terms for son of bitch, 1 data of racist for Nigger, 3 data of animal terms of rats, chicken, and cat, and 6 data of sexual irregulities for tart and bitch. It is also, 5 kinds of swearword translation techniques in the research, they are 9 data of literal translation, 1 data of particularization, 1 data of reduction, 3 data of transposition and 1 data of adaptation